I - Ecologically responsible and efficient recycling of Pd from aqueous effluents using biosorption on biomass feedstock. (25th May 2021) - Garcia, Armelle; Deyris, Pierre-Alexandre; Adler, Pauline; Pelissier, Franck; Dumas, Timothé; Legrand, Yves-Marie; Grison, Claude
Abstract: In the current context of the considerable interest in palladium (Pd), a new process of Pd biosorption is described with various natural materials derived from plant feedstocks. Eichhornia crassipes was chosen as a model plant for determining the thermodynamic and kinetic parameters of Pd biosorption. The optimised process was then tested on other natural materials (wheat, pine cones, coffee grounds, green tea grounds), powders derived from dead native ( Mentha aquatica) and invasive aquatic plants ( Pistia stratiotes, Ludwigia peploides) . The competitive biosorption of other platinum group metals, i.e. Pd, Ru, Ir, Rh, Pt) was also evaluated using E. crassipes . Moreover, selective separation of Pd, Pt, Ru and Ir was possible. Mechanistic investigations allowed us to explain the high affinity of Pd for root powder obtained from aquatic plants. Highlights: Root powders derived from aquatic plants as biosorbents of Pd. An efficient ecotechnology to recycle PGM with a selective separation of Pd, Pt, Ru, Ir. An opportunity for the recovery of invasive aquatic plants. A strong motivation for their harvest and the control of their proliferation. New natural materials for the preparation of ecocatalysts in organic synthesis.